Cassia tora Linn Cream Inhibits Ultraviolet-B-Induced Psoriasis in Rats. (25th March 2012) - Singhal, Manmohan; Kansara, Niraj
Abstract : The aim of present study was to determine the antipsoriatic activity of newly formulated O/W creams of methanolic extract of Cassia tora L. leaves by using ultraviolet-B-induced psoriasis in rat. The plant Cassia tora L. is traditionally claimed to be useful in the treatment of a number of skin diseases. However, there are no established scientific reports for its antipsoriatic activity. Methanolic Cassia tora L. leaves extract was used to prepare various concentrations of O/W creams and tested for acute dermal toxicity study. The different O/W creams showed good physical characteristics and passed the sensitivity, irritation, grittiness and bleeding test. The results of acute dermal toxicity showed that the creams were safe up to the dose of 2000 mg/kg. In case of psoriasis model, histopathological analysis revealed that there were absence of Munro's microabscess, elongation of rete ridges, and capillary loop dilation in the section in Test 2 (0.1%) and standard group. O/W creams and methanolic extract of Cassia tora L. leaves exhibited significant reduction in percentage of relative epidermal thickness and spleen index as compared to positive control. We concluded that topical O/W creams and crude extract containing methanolic extract of Cassia tora L. leaves have potent antipsoriatic activity in ultraviolet-B-induced psoriasis in rat.